2019
DOI: 10.13080/z-a.2019.106.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic and mineral fertilisers on maize nitrogen nutrition indicators and grain yield

Abstract: The study examined the effect of organic and mineral fertilisers on soil nitrogen (N) supply, maize grain productivity and correlation of mid-season plant and soil indicators with grain yield and soil mineral nitrogen (N min) at harvest. Field experiments using the short-season maize (Zea mays L.) cultivar 'Agiraxx' were conducted in 2015-2017 on a sandy loam soil in Central Lithuania. Prior to sowing, the soil was applied with 170 kg ha-1 of N as ammonium nitrate, pelletized cattle manure (PCM), pelletized po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The obtained digestate after anaerobic digestion could be used as an organic fertiliser for the fields of the farm [ 28 , 29 , 30 , 31 ]. The composition of the mixture of fish co-streams with cattle manure should be formed as nutrients for plant fertilisation [ 32 , 33 ]. Co-digestion of fish co-streams with cattle manure could improve the energy efficiency of biogas plant and fertilisation quality of the final digestate [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The obtained digestate after anaerobic digestion could be used as an organic fertiliser for the fields of the farm [ 28 , 29 , 30 , 31 ]. The composition of the mixture of fish co-streams with cattle manure should be formed as nutrients for plant fertilisation [ 32 , 33 ]. Co-digestion of fish co-streams with cattle manure could improve the energy efficiency of biogas plant and fertilisation quality of the final digestate [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The regular supply of nutrients during the cropping period, close synchronization between nutrient release/crop demand and improvements in the important properties of amended soils could be possible causes for the considerable increase in growth and yield obtained with saffron under UN + PM treatment, as observed by Ghanbarian et al (2008). Other studies (Enujeke 2013, Adeyeye et al 2107, Zydelis et al 2019) also showed that the soil application of organic materials, particularly PM, has the potential to sustain crop yields and improve soil properties and fertility. Moreover, Koocheki et al (2019) discussed the positive effects of organic matter amendments or content on stigma and daughter corm yield of saffron.…”
Section: Discussionmentioning
confidence: 92%
“…The yield attributes serve as reliable indicators of saffron yield, and our findings were in line with those of Ewulo et al (2008) and Koocheki et al (2019), who opined that crop yields were increased through PM application because of its leading role in enhancing nutrient content and uptake. Increased growth and yield attributes (SY and CY) in the combined N and PM treatments could be the result of microbial N mineralization from the PM providing N during the whole growing period in proportion to crop requirement (Zydelis et al 2019).…”
Section: Corm Yield Of Saffronmentioning
confidence: 99%
“…The chemical composition of plant-based organic fertilisers. Plant nutrition in arable farms can be enriched by using organic fertilisers, although their function and the satisfaction of crop demand are highly dependent on the type or chemical composition (Chen et al, 2018;Žydelis et al, 2019). The fresh red clover mass can accumulate a high N amount (Brozyna et al, 2013;Frøseth et al, 2014;Gaudin et al, 2013), but the process of N accumulation and release is difficult to predict and control.…”
Section: Discussionmentioning
confidence: 99%